John Dewey on philosophy of experience and human education - Darcísio Natal Muraro (Universidade Federal de Santa Catarina, 2017)
The objective of this study is to investigate the conception of philosophy and its relation to human formation in the thinking of John Dewey. The work aimed at analyzing the concepts in the main works of the author and his interpreters. The paper analyzes the reconstruction of philosophy as a philosophy of experience anchored in the genetic, experimental, reflexive, critical and creative method. The philosophy of experience is opposed to the dualisms and the spectator philosophies of knowledge that maintains the social division into classes. The role of the philosophy of experience is to rationalize through inquiry the possibilities of human experience through the critical reconstruction of the meanings. The philosophy of experience is a condition of possibility for democratic life and for an education based on freedom and human emancipation.